Molecular and cytogenetic identification of new wheat-Dasypyrum breviaristatum additions conferring resistance to stem rust and powdery mildew - Liu, Cheng (Breeding science, 2011)
Two cytologically stable wheat-Dasypyrum breviarisatatum addition lines, Y93-1-6-6 and Y93-1-A6-4, were identified by integrated molecular and cytogenetic techniques. C-banding and genomic in situ hybridization (GISH) showed that Y93-1-6-6 and Y93-1-A6-4 were different wheat-D. breviaristatum additions. A total of 51 markers (primer/enzyme combinations), including 6 PCR-based Landmark Unique Gene (PLUG) markers and 45 Sequence-Tagged-Site (STS) markers, were selected from 3,774 primer/enzyme combinations to further characterize these two additions. Marker haploytpes suggested that both D. breviaristatum chromosomes in Y93-1-6-6 and Y93-1-A6-4 were rearranged. Stem rust resistance screening indicated that both additions were highly resistant to race RKQQC, whereas only Y93-1-6-6 was resistant to race TTKSK (Ug99). Powdery mildew resistance screening showed that only Y93-1-6-6 was resistant. Pedigree analysis suggested that the stem rust and powdery mildew resistance of Y93-1-6-6 was derived from D. breviaristatum, indicating that the D. breviaristatum chromosomes in Y93-1-6-6 possess a new powdery mildew resistance gene(s), and new stem rust resistance gene(s). These two additions could be used as stem rust or powdery mildew resistance sources in wheat breeding programs